FINANCE LEASE AS AN OBJECT OF ACCOUNTING: RECOGNITION, MEASUREMENT AND PRESENTATION - Bezverkhyi, Kostiantyn; Yurchenko, Oleksandr; Golub Natаliia (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and methodological foundations of accounting for finance leases in the context of a modern economic environment characterized by instability, limited investment resources, and the need to renew fixed assets. Finance leasing is substantiated as an effective tool for attracting investment and ensuring asset modernization without significant initial financial burden. At the same time, the study identifies key challenges in leasing practice, including inconsistencies in the interpretation of its economic substance, lack of unified approaches to defining accounting objects, and discrepancies between accounting and tax regulations. It is determined that finance leasing combines elements of investment, credit, and asset use, which complicates its accounting treatment. The study emphasizes the importance of applying the principle of substance over form, as finance leases involve the transfer of substantially all risks and rewards to the lessee. The accounting process is presented as a sequence of stages—observation, measurement, recording, systematization, and summarization—each contributing to the formation of reliable accounting information. Special attention is given to the criteria for recognizing leases as finance leases under accounting standards and tax legislation. Core indicators include transfer of ownership, bargain purchase options, lease term duration, and the relationship between present value of lease payments and fair value of the asset. The study also highlights differences between accounting and tax approaches. Key accounting categories are systematized, including guaranteed and unguaranteed residual values and minimum lease payments. It is established that lease payments have an annuity structure and consist of asset repayment and financial income. The present value of lease payments is defined through discounting, forming the basis for financial results recognition. The article demonstrates symmetrical accounting treatment: the lessee recognizes an asset and liability, while the lessor records receivables and financial income. This ensures consistency of financial results and reflects the economic nature of leasing transactions. The findings contribute to improving accounting methodology and enhancing the quality of financial information for management decisions. Further research should focus on evaluating leasing efficiency and adapting accounting approaches to digital environments.